PERAN GURU DALAM MENINGKATKAN MOTORIK HALUS PADA ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK LEMBAGA KESEJAHTERAAN IBU DAN ANAK II PONTIANAK - Eni Ika Mardiana; Muhamad Ali; Dian Miranda (Universitas Tanjungpura, 2021)
AbstractThis study aims to determine the teacher's role in improving the fine motor skills of children aged 5-6 years in Kindergarten Mother and Child Welfare Institution II Pontianak. The research method used is descriptive with a qualitative research form, sources of data in this study were the principal, class B teachers, parents of children. The data collection technique uses interview, observation, and documentation techniques, the results of this study show the role of the teacher as a motivator, namely the teacher plays a role in providing motivation in increasing children's interest, giving rewords to children such as stars, stickers, applause, and giving encouragement in the form of words such as kudos, great boy. Furthermore, the role of the teacher as a facilitator is that the teacher provides facilities to good children who study at home at home and at school, to improve fine motor skills the teacher provides tools and materials, the role of the teacher as an evaluator is that the teacher always has standards in the assessment (BB, MB, BSH, BSB), the teacher always evaluates the results of children's work and when children study at school class.Keywords: Teacher Role and Fine Motor